2022
DOI: 10.1021/acsaem.1c03569
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of Interface and Bulk Properties in Cu2ZnSn(S,Se)4 Thin-Film Solar Cells with Ultrathin CuAlO2 Intermediate Layer and Ge Doping

Abstract: Recently, kesterite-based absorbers and related compounds have been considered as promising eco-friendly light absorber materials for thin-film solar cells (TFSCs). However, the device performances of kesterite-based TFSCs are limited because of the formation of defects and poor interfacial properties. In this study, we developed a strategic approach to improve the device performances of Cu 2 ZnSn(S,Se) 4 (CZTSSe) solar cells using back-interface passivation of the absorber layer and further reduced the format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…The detailed kesterite CZTSSe absorber thin‐film preparation, device fabrication, and characterization techniques used in this study can be found in the Supporting Information and our previous reports. [ 21,41 ]…”
Section: Methodsmentioning
confidence: 99%
“…The detailed kesterite CZTSSe absorber thin‐film preparation, device fabrication, and characterization techniques used in this study can be found in the Supporting Information and our previous reports. [ 21,41 ]…”
Section: Methodsmentioning
confidence: 99%
“…37 Precursors were deposited from individual metallic targets in stacked layers, i.e., Zn (bottom)/Sn/ Cu(top), using the direct-current (DC) magnetron sputtering method. For double-cation doping, i.e., Ag (8 nm) 27 and Ge (10 nm), 36 ultrathin layers were deposited individually at different stages (Ge at the bottom and Ag at the top of the precursor) using the thermal evaporation method. The precursors and Ag-Ge-doped samples were then so annealed at 300 °C for 60 min in an Ar atmosphere at a ramping rate of 10 °C min −1 to achieve Cu-Zn and Cu-Sn alloys with smooth morphologies.…”
Section: Methodsmentioning
confidence: 99%
“…To achieve this, we used individually optimized doping conditions such as thickness and position for the Ag and Ge cations. 20,27,36 The deposition of Ag and Ge at the top and bottom of the precursor, respectively, improved the device performance under standard test conditions more than the undoped CZTSSe device. Further, a similar device tested under different light intensity conditions of white LED (WLED) and uorescent lamps (4000 K) (FL-4000K) revealed improved V oc losses with higher PCE outputs for the CZTSSe:Ag-Ge device.…”
Section: Introductionmentioning
confidence: 99%
“…Various materials, including metals, [138,139] metal oxides, [140][141][142] metal chalcogenides, [95] metal nitride, [143,144] organic, [49,145,146] and other non-organic materials, [147,148] have been proposed as effective intermediate layers between Mo and kesterite. Gour et al reported 10.54% efficiency CZTSSe solar cells by introducing a 1.2 nm CuAlO 2 (CAO) nanolayer at the back interface.…”
Section: Intermediate Layersmentioning
confidence: 99%
“…Various materials, including metals, [ 138,139 ] metal oxides, [ 140–142 ] metal chalcogenides, [ 95 ] metal nitride, [ 143,144 ] organic, [ 49,145,146 ] and other non‐organic materials, [ 147,148 ] have been proposed as effective intermediate layers between Mo and kesterite. Gour et al.…”
Section: Back Contact Interface Engineeringmentioning
confidence: 99%